From Mourning to Manipulation: Navigating the Psychological Terrain of AI Grief Therapy - Evan Bose; Chaitanya Anil Kumar; Meenakshi N. (International Journal of Behavioral Sciences, 2025)
This literature review explores the psychological and ethical dimensions of virtual conversations with AI-based digital representations of deceased individuals. Specifically, it examines the therapeutic affordances of these interactions, as well as potential maladaptive coping mechanisms, including prolonged mourning, emotional exploitation, and memory distortion. Based on a review of 13 academic studies from 2021 to 2024, this paper critically analyzes ethical dilemmas related to informed consent, data commodification, and the autonomy of grieving individuals. Digital afterlife technologies, often utilized for grief therapy, significantly impact the grieving process by allowing sustained, albeit artificial, interaction with loved ones. The review draws attention to the mixed nature of these technologies, recognizing their potential to offer comfort but also expressing worries about how they can worsen emotional dependence or obstruct normal grieving processes. It investigates the ways in which cultural norms and individual values impact people's experiences with these tools, illuminating a range of responses in various demographic and cultural contexts. Along with the significance of protecting vulnerable users' emotional wellbeing, the ethical dilemmas raised by the monetization of personal data and the possibility of consent violations are also thoroughly investigated. The review also considers the cultural context of grief, with a focus on how cultural relativism shapes attitudes toward digital afterlife practices. The study ends with suggestions for creating ethical standards and legal frameworks to lessen any risks, highlighting the necessity of interdisciplinary cooperation and more study to fill in the gaps in this developing sector.
Keywords: Therapeutic affordances; digital afterlife; emotional exploitation; grief practices; prolonged mourning